Wage Inequality in the United Kingdom, 1975-99 - Prasad, Eswar (IMF Working Papers; Working Paper, 2002)
This paper provides evidence that cross-sectional wage inequality in the U.K. rose sharply in the 1980s, continued to rise moderately through the mid-1990s and has remained essentially unchanged since then. As in the U.S., increases in within-group inequality account for a substantial fraction of the rise in wage dispersion during 1975-99. Compositional shifts in the occupational and industry structures of aggregate employment are also shown to have had important effects on the evolution of wage inequality. The convergence of the wage distributions for men and women has, however, had a stabilizing effect on the overall wage distribution.